Analisis Klaster Menggunakan Metode Average Linkage dengan Validasi Multiscale Bootstrap (Studi Kasus: Indikator Pendidikan di Indonesia Tahun 2021) - Rasidia, Fikri; Roejantoro, Rito; Fathurahman, Muhammad (EKSPONENSIAL, 2025)
The average linkage method is one of the hierarchical cluster analyses, where the clustering process starts by finding two objects that have the closest distance to the average rule of the two groups. The multiscale bootstrap method is a method used to see the validity of the cluster analysis results. This study aims to determine the clusters formed using the average linkage method, as well as to determine the validity of the clusters formed based on education indicators in each province in Indonesia. The result of the study is one cluster with AU (Approximately Unbiased) ≥ 0.95 so that the cluster is considered to be able to represent the actual population.